Implementasi Media Puzzle aalam Evaluasi Hafalan Al-Qur’an Siswa Kelas V di SDIT BAIK (Bina Anak Islam Krapyak) Yogyakarta - Iftakhuzzulfa, Andita; Ru'iya, Sutipyo (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2025)
This study aims to implement puzzle media in the memorization evaluation of fifth graders at SDIT BAIK Yogyakarta. In addition, the researcher also wants to determine the effectiveness of puzzle media used as a medium for evaluating Al-Qur'an memorization. This study uses a qualitative research method sourced from one tahfidz teacher and one tahfidz teacher coordinator. Data collection techniques were collected through observation, direct observation, documentation, and interviews. The data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. To test the validity of the data, continuous observation was carried out. The results of this study were obtained through several stages: planning, implementation, and evaluation of the use of puzzle media in improving the quality of student memorization. First, the planning stage was well-organized, evidenced by the teacher's preparation before conducting learning in the use of puzzle media. Second, at the implementation stage, the use of puzzle media can be implemented well, carried out by groups and individuals with the aim of achieving the quality of student memorization. Third, at this stage each student is measured through the results of the evaluation that has been carried out by the teacher through an evaluation test in compiling the puzzle media.